Case study on the costume and wardrobe development of selected Philippine Independent Film productions - Lemence, Aien Mae G.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT Clothing used as costume and wardrobe enhance a film?s narrative. However, there is a lack of literature and references about costume design and wardrobe development in films in both international and local settings. Consequently, there is a lack of awareness and appreciation for the work of the costume designer and the wardrobe head. In order to give an appreciation to them, this study described the present condition of costume and wardrobe development in Philippine independent film productions by: (1) explaining the level of involvement, qualifications, responsibilities, and perception of people from the industry, (2) describing the stages in costume and wardrobe development, and (3) analyzing the factors that affect the costume and wardrobe decisions. Through snowball purposive sampling, the researcher interviewed individuals who have worked in the local independent film industry. The researcher was able to conceptualize different organizational structures that explain the work of the Costume Designer, Wardrobe Head, Wardrobe Stylist, and the ?Wardrobe.? These are the job titles of those responsible for the costume and wardrobe development. It was found that there is a conflict between the perception of the respondents regarding the knowledge and capabilities as it relates to the creative and technical contributions of the people involved in wardrobe and costume. Nevertheless, most of the respondents agree their works should be recognized. It was also found that the process of costume and wardrobe development in local independent films is similar to the mainstream production such as Hollywood films. There are a number of factors that affect the development of costume and wardrobe such as the film narrative, time frame, sourcing, and budget. As an exploratory research, the researcher recommended topics that could be further studied, as well as topics that could be integrated in the BS Clothing Technology course.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Costume design -- Philippines